2018
DOI: 10.1111/bph.14179
|View full text |Cite
|
Sign up to set email alerts
|

Ebselen has lithium‐like effects on central 5‐HT2A receptor function

Abstract: Our data demonstrated lithium-mimetic effects of ebselen in different experimental models of 5-HT receptor function, probably mediated by IMPase inhibition. This evidence of lithium-like neuropharmacological effects of ebselen adds further support for the clinical testing of ebselen in mood disorders, including as an antidepressant augmenting agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 61 publications
(102 reference statements)
2
17
0
Order By: Relevance
“…Our previous studies (Singh et al, 2013; Antoniadou et al, 2018) identified that ebselen had various neuropharmacological actions similar to those reported for lithium in preclinical models, and the present study extends this to impulse control. Thus, in the 5-CSRTT, the inhibition of premature responding by ebselen was observed at more than one dose, and under conditions of elevated premature responding as induced by cocaine.…”
Section: Discussionsupporting
confidence: 85%
“…Our previous studies (Singh et al, 2013; Antoniadou et al, 2018) identified that ebselen had various neuropharmacological actions similar to those reported for lithium in preclinical models, and the present study extends this to impulse control. Thus, in the 5-CSRTT, the inhibition of premature responding by ebselen was observed at more than one dose, and under conditions of elevated premature responding as induced by cocaine.…”
Section: Discussionsupporting
confidence: 85%
“…More recently, ebselen has been suggested as an antidepressant (Antoniadou et al 2018 ) and impulsivity lowering agent (Barkus et al 2018 ) based on its neuropharmacological lithium-like effects in different animal models of 5-HT2A function. Therefore, Fink and collaborators reported that elevated 5-HT2A receptor expression is associated with impulsive behavior in rodents (Fink et al 2015 ).…”
Section: Pharmacology Of Organoselenium Compoundsmentioning
confidence: 99%
“…Nevertheless, it has been argued that the negative emotionality phenotype seen in 5-HTTKO mice is of neurodevelopmental origin rather than due to elevated 5-HT availability at the time of behavioral testing 30,31,46 . Citalopram causes a marked elevation of 5-HT availability, as shown by microdialysis 47 , and here we tested whether this elevation was sufficient to affect fear learning or memory. We did not use chronic SSRI administration because this can cause widespread changes to neuronal circuitry (e.g., increasing neurogenesis, altering the expression/function of other 5-HT receptors) 48,49 , and we wanted to test the effects of increasing 5-HT availability on fear learning/memory without these potential confounds.…”
Section: Discussionmentioning
confidence: 94%